Differences in Knowledge, Awareness, Practice, and Health Symptoms in Farmers Who Applied Organophosphates and Pyrethroids on Farms - Thammachai, Ajchamon; Sapbamrer, Ratana; Rohitrattana, Juthasiri; Tongprasert, Siam; Hongsibsong, Surat; Wangsan, Kampanat (Frontiers in Public Health, 2022)
Objective This cross-sectional study aimed to examine farmers' knowledge, awareness, practices regarding pesticide use, and prevalence of health symptoms related to pesticides exposure among farmers who applied organophosphates (OP) and pyrethroids (PY). Methods Data regarding demographic variables and health symptoms pertinent to pesticide use was collected from 67 farmers who applied OP and 50 farmers who applied PY using interviews from January to March 2021. Results The farmers who applied OP had lower knowledge, awareness, and prevention practices regarding pesticide use than those who applied PY. After adjustment of covariate variables, the farmers who applied OP had a significantly higher prevalence of respiratory conditions (OR = 8.29 for chest pain, OR = 6.98 for chest tightness, OR = 27.54 for dry throat, and OR = 5.91 for cough), neurological symptoms (OR = 10.62 for fatigue and OR = 6.76 for paresthesia), and neurobehavioral symptoms (OR = 13.84 for poor concentration, OR = 3.75 for short term memory, and OR = 8.99 for insomnia) related to pesticide exposure than those who applied PY. Conclusion Our findings suggest that OP had a more adverse effect on human health than PY, resulting in a higher prevalence of pesticide-related symptoms. The outcomes of this study have the benefit of providing vital information for all stakeholders with regard to the implementation of safe practices in the utilization of personal protective equipment (PPE) and pesticide use in a health intervention and health promotion program.